Dostęp do szkolnictwa wyższego – od orientacji na elitę poprzez demokratyzację do parentokracji - Sobczak, Anna (Studia Edukacyjne, 2018)
The article aims to describe the changes that have taken place in access to higher education over the years. The author began her reflections from ancient times, when higher education was initiated, and ends in modern times, characterized by mass education at a higher level. The article points out that the university and higher education system has undergone many transformations over the centuries, and elite studies have evolved into egalitarian ones. The phenomenon of parentocracy, which is more and more common in the current conditions of general education in higher schools, is also discussed.